2014
DOI: 10.1038/tp.2014.124
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal structural and functional changes associated with electroconvulsive therapy response

Abstract: Previous animal models and structural imaging investigations have linked hippocampal neuroplasticity to electroconvulsive therapy (ECT) response, but the relationship between changes in hippocampal volume and temporal coherence in the context of ECT response is unknown. We hypothesized that ECT response would increase both hippocampal resting-state functional magnetic resonance imaging connectivity and hippocampal volumes. Patients with major depressive disorder (n=19) were scanned before and after the ECT ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
173
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(201 citation statements)
references
References 54 publications
16
173
4
Order By: Relevance
“…This is in line with previous studies (Nordanskog et al, 2010;Tendolkar et al, 2013;Abbott et al, 2014;Dukart et al, 2014;Nordanskog et al, 2014;Bouckaert et al, 2015;Jorgensen et al, 2015;Ota et al, 2015;Sartorius et al, 2016). Only two studies found an association between hippocampal volume increase and therapeutic efficacy (Dukart et al, 2014;Joshi et al, 2015).…”
Section: Relationship Between Depressive Symptomatology and Hippocampsupporting
confidence: 92%
See 2 more Smart Citations
“…This is in line with previous studies (Nordanskog et al, 2010;Tendolkar et al, 2013;Abbott et al, 2014;Dukart et al, 2014;Nordanskog et al, 2014;Bouckaert et al, 2015;Jorgensen et al, 2015;Ota et al, 2015;Sartorius et al, 2016). Only two studies found an association between hippocampal volume increase and therapeutic efficacy (Dukart et al, 2014;Joshi et al, 2015).…”
Section: Relationship Between Depressive Symptomatology and Hippocampsupporting
confidence: 92%
“…Moreover, the hippocampus and brain regions that mediate emotional and cognitive regulation are anatomically connected, lending support to the role of the hippocampus in depressionrelated circuitry (Price and Drevets, 2010;Abbott et al, 2014). Several recent magnetic resonance imaging (MRI) studies have described hippocampal volume changes following ECT (Nordanskog et al, 2010;Tendolkar et al, 2013;Abbott et al, 2014;Dukart et al, 2014;Nordanskog et al, 2014;Joshi et al, 2015;Jorgensen et al, 2015;Ota et al, 2015;Bouckaert et al, 2015;Sartorius et al, 2016).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, recent functional magnetic resonance imaging (MRI) studies of ECT in depression have shown some laterality of neuronal connectivity of HPC. That is, the right hippocampal connectivity with the left superior temporal lobe increased after an ECT series and correlated with the amelioration of depressive symptom, but no such increase in the left hippocampal connectivity with any brain regions was found (Abbott et al, 2014).…”
Section: Introductionmentioning
confidence: 92%
“…Recent neuroimaging studies have revealed structural and functional differences in the human brain before and after an ECT series (Dukart et al, 2014;Jorgensen et al, 2016;Ota et al, 2015). Some studies have shown an increase in the GM volume of bilateral HPCs after ECT (Jorgensen et al, 2016;Ota et al, 2015); others have shown that an ECT series significantly contributes to the increase in the GM volume of the right HPC, but not to that of the left HPC (Dukart et al, 2014;Abbott et al, 2014). Moreover, recent functional magnetic resonance imaging (MRI) studies of ECT in depression have shown some laterality of neuronal connectivity of HPC.…”
Section: Introductionmentioning
confidence: 99%